Analisis Faktor-Faktor Yang Mempengaruhi Turnover Intention Agent di PT AIA Cabang X Malang - Lidia Halim; Kevin Antolis (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Turnover intention is a problem that is often faced by companies and employees. Turnover intention needs to be a center of attention because high turnover intention can disrupt the activities and productivity of companies and employees. In PT AIA Branch X Malang there are several factors that cause turnover intention. The purpose of this study was to find out what factors influenced the turnover intention of the agent at PT AIA Branch X Malang. This research was a quantitative study with a confirmatory research approach. The data analysis technique used was factor analysis. Respondents studied in this study were 202 people from 202 population in PT AIA Branch X Malang. The results of this study indicated that all work life balance variables, personality-job fit, work stress, employee relations, compensation, physical work environment, job satisfaction, organizational culture, career development, and organizational commitment affect the turnover intention of the agents at PT AIA Branch X Malang. The variable that has the most significant influence on turnover intention of the agents ata PT AIA Branch X Malang was organizational commitment and the variable that influence less significant namely work stress